Masonry infill walls in reinforced concrete frames as a source of structural damping - Özkaynak, Hasan; Yüksel, Ercan; Yalçın, Cem; Dindar, Ahmet Anıl; Büyüköztürk, Oral (Wiley-Blackwell, 111 River St, Hoboken 07030-5774, Nj Usa, 2014)
This paper presents the results of an experimental study on the determination of damping characteristics of bare, masonry infilled, and carbon fiber reinforced polymer retrofitted infilled reinforced concrete (RC) frames. It is well known that the masonry infills are used as partitioning walls having significant effect on the damping characteristics of structures as well as contribution to the lateral stiffness and strength. The main portion of the input energy imparted to the structure during earthquakes is dissipated through hysteretic and damping energies. The equivalent damping definition is used to reflect various damping mechanisms globally. In this study, the equivalent damping ratio of carbon fiber reinforced polymer retrofitted infilled RC systems is quantified through a series of 1/3-scaled, one-bay, one-story frames. Quasi-static tests are carried out on eight specimens with two different loading patterns: one-cycled and three-cycled displacement histories and the pseudo-dynamic tests performed on eight specimens for selected acceleration record scaled at three different PGA levels with two inertia mass conditions. The results of the experimental studies are evaluated in two phases: (i) equivalent damping is determined for experimentally obtained cycles from quasi-static and pseudo-dynamic tests; and (ii) an iterative procedure is developed on the basis of the energy balance formulation to determine the equivalent damping ratio. On the basis of the results of these evaluations, equivalent damping of levels of 5%, 12%, and 14% can be used for bare, infilled, and retrofitted infilled RC frames, respectively. Copyright (c) 2013 John Wiley & Sons, Ltd.
Keywords: energy methods; masonry infilled frames; equivalent damping; damping; CFRP retrofitting; Seismic Energy; Prediction; Tests